The MEDIATING ROLE OF CUSTOMER SATISFACTION IN THE RELATIONSHIP BETWEEN TRUST, EMOTIONAL BONDING, AND LOYALTY: EMPIRICAL EVIDENCE FROM AN SME AUTOMOTIVE WORKSHOP - Apriansyah, Roky; Hermanto (Management Department, Faculty of Economics and Business, Universitas Jambi, 2026)
This study aims to analyze the role of customer satisfaction in mediating the influence of trust and emotional bonding on customer loyalty at Bengkel Putra Motor. Amidst the intense competition in the automotive service sector, understanding the drivers of customer retention is critical for the long-term sustainability of small and medium enterprises (SMEs). This research employs a quantitative approach with a correlational design. Data were collected from 100 respondents using purposive sampling. Structural Equation Modeling (SEM) based on Partial Least Squares (PLS-SEM) was utilized to test the hypothesis and the mediating role of customer satisfaction. The results indicate that trust and emotional bonding have a significant positive influence on customer satisfaction and customer loyalty. Furthermore, customer satisfaction acts as a significant partial mediator between trust, emotional bonding, and customer loyalty. The findings suggest that while trust and emotional bonding are essential predictors, customer satisfaction is the most dominant driver of loyalty, serving as the vital mechanism to convert psychological commitment into behavioral loyalty. The study provides empirical evidence that Bengkel Putra Motor should focus on strengthening technical transparency to foster trust and cultivate emotional engagement to enhance customer experience. By optimizing these factors, the enterprise can mitigate customer churn and ensure long-term business sustainability. This research contributes to the literature on relationship marketing by integrating emotional bonding and trust within a unified mediation model in the specific context of an SME automotive workshop, addressing the research gap regarding customer retention strategies in local service entities.